Effect of Reactive and Non-Reactive Diluent on Mechanical Properties of Epoxy Resin - Aras, Ömür; Kaya, Yunus (Bilecik Şeyh Edebali Üniversitesi, 2021)
Epoxy resins, which are frequently preferred among thermoset plastics in the industry, are materials with high viscosity, and good mechanical performance. The biggest disadvantage of epoxy resins is that they encounter difficulties in application alone due to their high viscosity. For this reason, various diluents are added to reduce their viscosity and applications are conducted. In this study, the mechanical properties of the epoxy resin, which is used in many fields, were observed with the addition of certain sizes of reactive and non-reactive diluents. Diglycidyl ether was used as the reactive diluents, and benzyl alcohol was used as the non-reactive diluent. In addition, ethylene diamine and diethylene triamine were used as curing agents. It was tried to determine the optimum modification of the hardened epoxy resin by measuring the mechanical strengths in the electromechanical test device. The results indicated the optimum composition that does not dramatically affect the mechanical performance of the epoxy resin is the composition containing 7.5% DE and 10% EDA, its tensile strength measured as 53.27 N/mm2.

Endüstride termoset plastikler arasında sıklıkla tercih edilen epoksi reçineler yüksek viskoziteye sahip, mekanik performansları oldukça iyi olan malzemelerdendir. Epoksi reçinelerinin en büyük dezavantajı, yüksek viskoziteleri sebebiyle tek başlarına uygulamada zorluklar ile karşılaşılmasıdır. Bu nedenle, viskozitelerini düşürmek amacıyla çeşitli diluentler eklenerek uygulamaları yapılmaktadır. Bu çalışma kapsamında birçok alanda kullanılan epoksi reçinenin, belirli ölçülerde reaktif ve reaktif olmayan seyreltici ilavesiyle mekanik özelliğindeki değişmeler gözlendi. Çalışmada reaktif diluent olarak diglisidil eter, non-reaktif diluent olarak ise benzil alkol kullanıldı. Kürleme ajanı olarak ise etilen diamin ve dietilen triamin kullanıldı. Sertleştirilmiş epoksi reçinenin elektromekanik test cihazında mekanik dayanımınları ölçülerek optimum modifikasyonu belirlenmeye çalışıldı. Elde edilen sonuçlar, epoksi reçinesinin mekanik performansını önemli ölçüde etkilemeyen optimum bileşimin % 7.5 DE ve % 10 EDA içeren bileşim olduğunu, bu numunenin gerilme mukavemetinin 53.27 N/mm2 olarak ölçüldüğünü gösterdi.
Reaktif ve Reaktif olmayan Seyreltici ilavesinin Epoksinin Mekanik Özelliklerine Etkisi